Analysis of Economic Competitiveness at Pandeglang Regency 2018-2023 - Akhmal Bahaduri, Aulia; Busnetty, Ida (Journal Corner of Education, Linguistics, and Literature, 2024)
This study aims to analyze and determine the basis of the competitiveness of the economic sector of Pandeglang Regency in 2018-2023 using the Location Quotient (LQ), Dynamic Location Quotient (DLQ), Shift Share, and Klassen Typology approaches. There are differences with previous studies, namely the area and time of the study. The results of the study using the LQ and DLQ methods show that there are five basic and prospective sectors, namely the Agriculture, Forestry, and Fisheries sectors; Mining and quarrying; Transportation and warehousing; Provision of accommodation and food and beverages; and Educational services. The processing industry sector shows great potential even though it has not become a basic sector. Based on the Klassen Typology analysis of Pandeglang Regency, five sectors are included in Quadrant I. The results of the Klassen typology analysis of Regencies/Cities in Banten Province show that Pandeglang Regency is relatively lagging in Quadrant IV. The results of the study using the shift share method show that the Mining and Quarrying sector is on average included in the non-progressive category, while the consistently progressive sectors are four sectors in a row. Based on the four analyses, the development of basic, progressive sectors, and the revitalization of lagging sectors have the potential to be key strategies in increasing regional economic competitiveness sustainably.